Communication, Language, and Modality in the Education of Deaf Students - Connie C. Mayer; Beverly J. Trezek (MDPI AG, 2023)
In the history of deaf education, questions attending communication, language, and modality have generated much discussion, and even heated debate. This should not be surprising as these questions touch on a fundamental issue that is central to policy and practice in the field-how to provide early, ready, and meaningful linguistic access. While one point of agreement is that such access is vital for age-appropriate language and literacy development, there is less consensus on how this access should be realized. This focus has heightened consequences and significance in the current context in which auditory access to spoken language is possible for the majority of deaf children. With a goal of reframing the conversation, the focus of this article will be on making the critical distinctions between language and modality that can inform understandings as to how access can be best achieved for an increasingly diverse population of deaf children and their families.